2022
DOI: 10.1002/ppsc.202200121
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and Irreversible HAuCl4 Binding to DNA for Seeded Gold Nanoparticle Growth and Opposite DNA and Aptamers Colorimetric Sensing Outcomes

Abstract: DNA‐directed seeded growth of gold nanoparticles has been used for the development of aptamer‐based biosensors with the assumption that target analytes can modulate the adsorption of aptamers to the gold seeds and thus affect the growth reaction. To understand the reaction, the effect of single‐ and double‐stranded DNA is first examined, and it is found that they have a similar promotion effect of anisotropic growth, suggesting that DNA cannot be detected using this method. By studying the interaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In a control test, we confirmed that the interferents themselves do not influence the dye color (SI, Figure S8). This contrasts with the use of gold nanoparticles as colorimetric probes, which produce a red-to-blue color change with virtually any nitrogen-containing interferent molecule. , Since fentanyl is often present at 1% by weight in drug samples, we then tested the dye-displacement assay with 1:100 (or 1:40) binary mixtures of fentanyl (5 μM) and another interferent (500 μM if solubility permitted, otherwise 200 μM) (Figure B). The assay was able to detect fentanyl in all mixtures, producing a clear purple-to-blue color change (SI, Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…In a control test, we confirmed that the interferents themselves do not influence the dye color (SI, Figure S8). This contrasts with the use of gold nanoparticles as colorimetric probes, which produce a red-to-blue color change with virtually any nitrogen-containing interferent molecule. , Since fentanyl is often present at 1% by weight in drug samples, we then tested the dye-displacement assay with 1:100 (or 1:40) binary mixtures of fentanyl (5 μM) and another interferent (500 μM if solubility permitted, otherwise 200 μM) (Figure B). The assay was able to detect fentanyl in all mixtures, producing a clear purple-to-blue color change (SI, Figure S9).…”
Section: Resultsmentioning
confidence: 99%